A Low-Cost Launch Assistance System for Orbital Launch Vehicles - Oleg Nizhnik (International Journal of Aerospace Engineering)
The author reviews the state of art of nonrocket launch assistance systems (LASs) for spaceflight focusing on air launch options. The author proposes an alternative technologically feasible LAS based on a combination of approaches: air launch, high-altitude balloon, and tethered LAS. Proposed LAS can be implemented with the existing off-the-shelf hardware delivering 7 kg to low-earth orbit for the 5200 USD per kg. Proposed design can deliver larger reduction in price and larger orbital payloads with the future advances in the aerostats, ropes, electrical motors, and terrestrial power networks.